Audit Efficiency and Effectiveness Consequences of Accounting System Homogeneity across Audit Clients: A New Form of Knowledge Spillover? - Murthy, Uday S.; Park, Jong Chool; Smith, Thomas; Whitworth, James (The Accounting Review, 2023)
ABSTRACT We examine the effects of a large number of clients in an audit office using the same enterprise-resource planning (ERP) system such as SAP or Oracle resulting in what we term “client accounting system homogeneity” on audit efficiency and effectiveness. Using a unique dataset of ERP system implementations, we find that accounting system homogeneity is positively associated with audit efficiency. Specifically, we find lower (higher) audit fees for clients using an ERP system from a vendor used by a higher (lower) proportion of clients in that office. We further document that accounting system homogeneity is associated with improved audit effectiveness as proxied by two accruals-based measures, incorrect internal control weakness reporting, and restatements. Our findings are reflective of a new form of knowledge spillover from repeated experiences auditing clients using similar accounting systems, resulting in audits that are not only less expensive but also of higher quality. Data Availability: Contact the authors.